Digital Storytelling of Physics (DiSPhy): Belajar Fisika melalui Cerita - Lari Andres Sanjaya; Eka Amelia Putri; Firmanul Catur Wibowo; Dimas Kurnia Robby; Ratna Widayanti Puspa D (Journal of Natural Science and Integration, 2021)
ABSTRACTThe role of learning media becomes very important in the period of distance learning to connect educators with learners. Therefore, the selection and use of learning media when Learning from Home (BDR) takes place will have an impact on the learning process that occurs. One of the practical and easy to use multimedia for BDR is Digital Storytelling. This article will present the results of research that produces digital storytelling of physics (DiSPhy) learning media that is equipped with science literacy and STEM projects. This research was conducted by the Research & Development (R&D) method which refers to the ASSURE steps. The resulting DiSPhy is tested directly to educators and learners using likert-scale questionnaire instruments. This research succeeded in producing digital learning media products in the form of DiSPhy equipped with decent science literacy as a medium of distance learning physics.Keywords: digital storytelling of physics, science literacy, learning from homeABSTRAK Peran media pembelajaran menjadi sangat penting pada masa pembelajaran jarak jauh untuk menghubungkan pendidik dengan peserta didik. Oleh karenanya, pemilihan dan penggunaan media pembelajaran saat Belajar dari Rumah (BDR) berlangsung akan berdampak pada proses pembelajaran yang terjadi. Salah satu multimedia yang praktis dan mudah digunakan untuk BDR adalah Digital Storytelling. Artikel ini akan memaparkan hasil penelitian yang menghasilkan media pembelajaran Digital Storytelling of Physics (DiSPhy) yang dilengkapi soal literasi sains dan proyek STEM. Penelitian ini dilakukan dengan metode Research & Development (R&D) yang mengacu pada langkah-langkah ASSURE. DiSPhy yang dihasilkan diuji secara langsung kepada pendidik dan peserta didik dengan menggunakan instrumen angket skala likert. Penelitian ini berhasil menghasilkan produk media pembelajaran digital berupa DiSPhy dilengkapi dengan soal literasi sains yang sangat layak sebagai media pembelajaran jarak jauh fisika.Kata kunci: digital storytelling of physics, literasi sains, belajar dari rumah